2018
DOI: 10.1186/s40795-018-0256-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional knowledge, dietary practice and associated factors among adults on antiretroviral therapy in Felege Hiwot referral hospital, Northwest Ethiopia

Abstract: Background: Nutritional support is identified as one of the most critical and immediate needs for people living with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). Adequate nutrition is vital to optimize response to medical treatment, manage opportunistic infections, maintain the immune system, and support optimal quality of life for people living with HIV/AIDS (PLWHA). Evidence has shown that the progression of the disease could be slowed with good nutrition. Nutrition interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…According to the current study, participants do not have the basic nutrition concepts and sought information from health professionals. This is in line with other study findings such as a study conducted in Felege Hiwot referral Hospital [ 8 ] which revealed that dietary counselling was a significant factor for nutritional knowledge and sought to have nutrition education and counselling should be given by health care workers for patients using ART to improve their nutritional knowledge. A study conducted in Addis Ababa revealed that factors related to low adherence were a low level of education; poor knowledge is helpful to adhere to food and nutrition programs [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…According to the current study, participants do not have the basic nutrition concepts and sought information from health professionals. This is in line with other study findings such as a study conducted in Felege Hiwot referral Hospital [ 8 ] which revealed that dietary counselling was a significant factor for nutritional knowledge and sought to have nutrition education and counselling should be given by health care workers for patients using ART to improve their nutritional knowledge. A study conducted in Addis Ababa revealed that factors related to low adherence were a low level of education; poor knowledge is helpful to adhere to food and nutrition programs [ 31 , 32 ].…”
Section: Discussionsupporting
confidence: 91%
“…HIV influences the well-being and prestige of a person. Moreover, the socio-economic well-being of individuals infected with HIV is adversely affected, and it also affects the economic growth of a country which in turn affects the development of a nation [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrition knowledge is important to improve the status of food security during an epidemic ( Florence and Valstar, 1999 ). This factor was identified as one of the most immediate needs for people living in a pandemic disease spread ( Mengie et al., 2018 ). The correlation between knowledge of nutrition and dietary diversity in Tehran province suggests the need to increase it among all households.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the result of the study relatively higher than the study conducted in Bahir Dar Felege Hiwot Referral Hospital and shows that, 21.7% had good nutritional knowledge among adults on ART [13] and Southwest Nigeria and shows that, 23.5% had good nutritional knowledge in women living with HIV/AIDS [14]. The difference of the results might be because of educational level, health service and awareness about the importance of nutrition.…”
Section: Discussionmentioning
confidence: 89%